2019
DOI: 10.18203/2349-3259.ijct20193213
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine treatment in viral-induced acute liver failure

Abstract: Background: Acute liver failure (ALF) is characterized by acute derangement of liver function and carries high mortality. Viral hepatitis is still one of the main causes of ALF in the India as well in world. A prospective case control study was carried with the aim to determine the effect of N-acetylcysteine (NAC) on survival of viral-ALF patients. Methods: 37 patients with a diagnosis of viral-ALF were included in the study. 18 patients received NAC infusion for 72 hrs whereas 19 patients in control group rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 30 publications
1
44
0
7
Order By: Relevance
“…Various studies have discussed the benefits of NAC in the treatment of acetaminophen induced acute liver failure. Despite significant limitations, a recent prospective randomised case control trial conducted in 2017 showed NAC along with conventional treatment benefitted the patient with non-acetaminophen induced acute liver failure 24. The patient in this report declined a liver biopsy, and therefore it was not possible to confirm the particular cause of acute liver failure.…”
Section: Discussionmentioning
confidence: 73%
“…Various studies have discussed the benefits of NAC in the treatment of acetaminophen induced acute liver failure. Despite significant limitations, a recent prospective randomised case control trial conducted in 2017 showed NAC along with conventional treatment benefitted the patient with non-acetaminophen induced acute liver failure 24. The patient in this report declined a liver biopsy, and therefore it was not possible to confirm the particular cause of acute liver failure.…”
Section: Discussionmentioning
confidence: 73%
“…The previous study by us showed that NAC improved the overall survival in non-acetaminophen induced ALF with a more favourable effect on drug-induced ALF. [21] Other studies also reported NAC improved transplant-free survival in early stage non-acetaminophen ALF(both in adults and childrens). [22,23] The non favourable effect of NAC in indeterminate ALF could be because indeterminate ALF had an advanced grade of encephalopathy (Gr III & IV) and subacute presentation which are related to poor prognosis.…”
Section: Discussionmentioning
confidence: 93%
“…Due to a lack of OLT facility, NAC has emerged as a beneficial treatment for non-paracetamol ALF. [21][22][23] Role of NAC in Viral-ALF has not been studied in controlled trials. So the prospective study was carried out to determine the role of NAC on mortality in indeterminate ALF and also to evaluate the safety and efficacy of NAC and its impact on the duration of hospital stay at a tertiary care centre in Kashmir (North India).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NAC is a thiol-containing agent that prevents hepatic damage by scavenging free oxygen radicals and replenishing glutathione stores [19,20]. It has anti-inflammatory, antioxidant, inotropic, and vasodilating properties that may help limit the toxicities from crizotinib [21,22]. e literature is not very clear about the benefit of using NAC in non-acetaminophen-induced acute liver failure (NAI-ALF).…”
Section: Discussionmentioning
confidence: 99%